Optimization of multi-environment trials for genomic selection based on crop models - R. Rincent; E. Kuhn; H. Monod; F.-X. Oury; M. Rousset; V. Allard; J. Le Gouis (Theoretical and Applied Genetics, 2017)

How the truffle got its mate: insights from genetic structure in spontaneous and planted Mediterranean populations of Tuber melanosporum - E. Taschen; F. Rousset; M. Sauve; L. Benoit; M.‐P. Dubois; F. Richard; M.‐A. Selosse (Molecular Ecology, 2016)
The life cycles and dispersal of edible fungi are still poorly known, thus limiting our understanding of their evolution and domestication. The prized Tuber melanosporum produces fruitbodies (fleshy organs where meiospores mature) gathered in natural, spontaneously inoculated forests or harvested in plantations of nursery‐inoculated trees. Yet, how fruitbodies are formed remains unclear, thus limiting yields, and how current domestication attempts affect population genetic structure is overlooked. Fruitbodies result from mating between two haploid individuals: the maternal parent forms the flesh and the meiospores, while the paternal parent only contributes to the meiospores. We analyzed the genetic diversity of T. melanosporum comparatively in spontaneous forests vs. plantations, using SSR polymorphism of 950 samples from South‐East France. All populations displayed strong genetic isolation by distance at the metric scale, possibly due to animal dispersal, meiospore persistence in soil, and/or exclusion of unrelated individuals by vegetative incompatibility. High inbreeding was consistently found, suggesting that parents often develop from meiospores produced by the same fruitbody. Unlike maternal genotypes, paternal mycelia contributed to few fruitbodies each, did not persist over years, and were undetectable on tree mycorrhizae. Thus, we postulate that germlings from the soil spore bank act as paternal partners. Paternal genetic diversity and outbreeding were higher in plantations than in spontaneous truffle‐grounds, perhaps because truffle growers disperse fruitbodies to maintain inoculation in plantations. However, planted and spontaneous populations were not genetically isolated, so that T. melanosporum illustrates an early step of domestication where genetic structure remains little affected.

Genome-wide association analysis to identify chromosomal regions determining components of earliness in wheat - J. Le Gouis; J. Bordes; C. Ravel; E. Heumez; S. Faure; S. Praud; N. Galic; C. Remoué; F. Balfourier; V. Allard; M. Rousset (Theoretical and Applied Genetics, 2012)

Grain characterization and milling behaviour of near-isogenic lines differing by hardness - V. Greffeuille; J. Abecassis; M. Rousset; F.-X. Oury; A. Faye; C. Bar L’Helgouac’h; V. Lullien-Pellerin (Theoretical and Applied Genetics, 2006)

‘Neighbourhood’ size, dispersal and density estimates in the prickly forest skink ( Gnypetoscincus queenslandiae ) using individual genetic and demographic methods - J. Sumner; F. Rousset; A. Estoup; C. Moritz (Molecular Ecology, 2001)
Dispersal, or the amount of dispersion between an individual’s birthplace and that of its offspring, is of great importance in population biology, behavioural ecology and conservation, however, obtaining direct estimates from field data on natural populations can be problematic. The prickly forest skink, Gnypetoscincus queenslandiae , is a rainforest endemic skink from the wet tropics of Australia. Because of its log‐dwelling habits and lack of definite nesting sites, a demographic estimate of dispersal distance is difficult to obtain. Neighbourhood size, defined as 4π D σ 2 (where D is the population density and σ 2 the mean axial squared parent–offspring dispersal rate), dispersal and density were estimated directly and indirectly for this species using mark–recapture and microsatellite data, respectively, on lizards captured at a local geographical scale of 3 ha. Mark–recapture data gave a dispersal rate of 843 m 2 /generation (assuming a generation time of 6.5 years), a time‐scaled density of 13 635 individuals * generation/km 2 and, hence, a neighbourhood size of 144 individuals. A genetic method based on the multilocus (10 loci) microsatellite genotypes of individuals and their geographical location indicated that there is a significant isolation by distance pattern, and gave a neighbourhood size of 69 individuals, with a 95% confidence interval between 48 and 184. This translates into a dispersal rate of 404 m 2 /generation when using the mark–recapture density estimation, or an estimate of time‐scaled population density of 6520 individuals * generation/km 2 when using the mark–recapture dispersal rate estimate. The relationship between the two categories of neighbourhood size, dispersal and density estimates and reasons for any disparities are discussed.

Comparative analysis of microsatellite and allozyme markers: a case study investigating microgeographic differentiation in brown trout ( Salmo trutta ) - A. ESTOUP; F. ROUSSET; Y. MICHALAKIS; J.‐M. CORNUET; M. ADRIAMANGA; R. GUYOMARD (Molecular Ecology, 1998)

Migration/selection balance and ecotypic differentiation in the mosquito Culex pipiens - C. CHEVILLON; Y. RIVET; M. RAYMOND; F. ROUSSET; P. E. SMOUSE; N. PASTEUR (Molecular Ecology, 1998)
Ecotypic differentiation is well described in the mosquito Culex pipiens , separating populations breeding in subterranean and human‐made sites (hypogeous habitat) from those in open‐air sites (epigeous habitat). The pattern of population differentiation observed at the Aat‐1 locus has been suspected to be associated with such ecotypic differentiation via habitat‐dependent selection, but this supposition is still the subject of debate in the literature. We analysed differentiation patterns for Aat‐1 and another four loci among populations from both habitat types in the French Alps. We showed that the Aat‐1 A allele is favoured within hypogeous habitats but selected against within epigeous habitats. Comparisons of our results with other data reported in the literature indicate that the Aat‐1 A allele is generally evolving under habitat‐differential selection, but that the precise balance of migration and selection that determines equilibrium allele frequencies varies greatly across Europe. The nature of this habitat‐dependent selection, and its resulting (geographically varying) equilibrium point, are discussed in relation to the biology of this mosquito species.